Delayed Leaf Senescence by Upregulation of Cytokinin Biosynthesis Specifically in Tomato Roots - Glanz-Idan, Noga; Lach, Michael; Tarkowski, Petr; Vrobel, Ondřej; Wolf, Shmuel (Frontiers in Plant Science, 2022)
Cytokinins (CKs) regulate numerous plant developmental processes, including photosynthesis and leaf senescence. Isopentenyltransferase (IPT) is a rate-limiting enzyme in the CK-biosynthesis pathway. We overexpressed ipt under tissue-specific promoters to study the long-range effect of CK on the functioning of tomato source leaves. Photosynthetic activity over time provided the measure for leaf aging. Significantly delayed leaf senescence was observed in plants expressing ipt under a root-specific promoter, but not in those expressing the gene under a source leaf-specific promoter. The root-derived influence on leaf aging was further confirmed by grafting experiments. CK concentration in source leaves of both transgenic lines increased significantly, with different proportions of its various derivatives. On the other hand, root CK concentration was only slightly elevated. Nevertheless, the significant change in the proportion of CK derivatives in the root indicated that CK biosynthesis and metabolism were altered. Partial leaf defoliation upregulates photosynthetic rate in the remaining leaf, however, overexpression of ipt in either tissues eliminated this response. Interestingly, Stem girdling also eliminated the photosynthetic response. Taken together, our findings suggest that leaf senescence is regulated by a CK-mediated root–shoot communication network. We propose that CK-mediated signal is translocated to the leaf via the xylem where it alters CK biosynthesis, resulting in delayed senescence.